Biotécnicas avançadas da reprodução de bovinos no APL lácteo do oeste goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
Much has been discussed about Brazil's importance on the world stage as a major food producer, making the case for the good results achieved with advanced bovine reproductive biotechnologies in the western Goiás dairy cluster, where we have seen an increase in our herd numbers, specificity for meat or milk and the ability to generate income and add value to the animals they produce. The aim of this review is therefore to take a detailed look at this important technology, showing how much it directly affects reproductive efficiency. It is estimated that we have 234 million head of cattle, making us the country that exports the most protein of animal origin with a significant figure of 2.2 million tons, according to Sense 2021, accounting for 14.4% of the world's exports. Artificial insemination was one of the first biotechnologies to be popularized in Brazil, managing to optimize the use of high genetic value males through the processing (freezing and marketing) of semen, spreading high value genetics throughout the country and the world, thus contributing significantly to the genetic advancement of the Brazilian herd, with artificial insemination being the most used biotechnology aimed at generating results in the medium and long term, where for example, in this work we had around 1. 143 inseminations were carried out, yielding 80% confirmed pregnancies. In addition, with the advent of embryo transfer, the interval between generations with high genetic value can be reduced, where it was possible to produce around 63 embryos during the time of this research. With these biotechnologies, it is possible to optimize the use of the female as a herd multiplier. In the beginning, ET was carried out by producing and harvesting embryos from the animal in vivo, then the Follicular Aspiration or OPU technique was developed. OPU made it possible to optimize the donor female, taking advantage of the recruitment of oocytes, as it consists of using equipment to obtain them by puncturing the ovary, and consequently the production of embryos takes place in vitro. In this way, we increase the number of embryos produced compared to the in vivo technique. Therefore, this review aims to address advanced reproductive biotechnologies and show how they directly affect reproductive efficiency.
Advanced biotechniques for cattle reproduction at APL dairy from western Goiás
Keywords: Embriões bovino; Fecundação; Folículo; Genética; Inseminação artificial; Produção animal; Artificial insemination; Bovine embryos; Fertilization; Follicle; Genetics; Animal production; CIENCIAS AGRARIAS